Peran Pelatih dalam Membina Prestasi Atlet Karate Dengan Metode Demonstrasi di Dojo Mardhatillah NW Penakak - M. Watoni; Didik Daniyantara; Zaenul Arkanuddin; Hariadi (Penerbit Jurnal Indonesia, 2025)
This study aims to find out the role of coaches in fostering the achievement of karate athletes using the demonstration method at Dojo Mardhatillah. A coach is a person whose task is to guide the trainee so that they master a skill in a particular field. A coach is a professional whose duty is to assist, guide, train, and direct talented athletes to achieve maximum performance in the shortest possible time. The method used in this study was a qualitative descriptive research approach with the aim of understanding the role of a coach in developing athlete achievement using the demonstration method. The results showed that the coach always provided examples before the athletes demonstrated the movements. Through the demonstration method, the coach was able to give athletes a clear picture so that they found it easier to understand and imitate the details of the movements.